Speech Acts Of Anxiety Used In Burnham’s Eighth Grade Film - Raflis Raflis; Sherina Azzahra Sherina Azzahra (Fakultas Sastra Universitas Ekasakti, 2026)
This research employs a pragmatic approach to analyze speech acts in the Eighth Grade by Bo Burnham. The primary objective is to identify the types of illocutionary acts used by the main character that reflect anxiety, as well as to determine the most dominant type of illocutionary act found in the film. The method used is observation, with data collection procedures involving: (1) downloading the film and its transcript, (2) watching the film while verifying the accuracy of the transcript against the spoken dialogue, (3) noting relevant utterances, and (4) classifying the speech acts based on the illocutionary act frameworks proposed by John Searle (1979) and George Yule (1996). The analysis is conducted descriptively to categorize the types of illocutionary acts and to identify which type is most frequently employed by the main character. The findings indicate a total of 56 speech acts in the film, consisting of 17 representative acts, 5 commissive acts, 10 directive acts, 1 declarative act, and 23 expressive acts. Among these, expressive acts are the most dominant, accounting for 23 utterances or 41.06% of the overall data.